Respuesta :

Answer:

x=14

Step-by-step explanation:

2(3x-4)=5x+6

first get rid of the parentheses by multiplying the  2

6x-8 = 5x+6

put like terms on one side of the equation. Start with the 5x, move it to the left side

(6x-8)-5x = (5x+6)-5x

x-8 = 6


Again, put like terms on one side of the equation. Move the 8 to the right side

(x-8)+8 = 6+8

=> x = 14


B)

4x - 3 = 2(x-1)

Start again by getting rid of the parentheses to make it a clean equation... aka distribute the 2:

4x-3 = 2x - 2

Move the like terms to one side of the equation. Start with x.. move 2x to the left:

(4x-3)-2x = (2x-2)-2x

=> 2x-3 = -2

Move the like terms to one side of the equation.Now move the -3 to the other side:

(2x-3)+3 = -2+3

=> 2x=1

Lastly, divide by 2 on both sides to find out what x is:

(2x)/2=1/2

=> x = 1/2


..so no, Charlie was incorrect.


Answer:

x=14

In the second line, he changed the sign on the 2

Step-by-step explanation:

2(3x-4) = 5x+6

Distribute the 2

6x-8 = 5x+6

Subtract 5x from each side

6x-5x -8 = 5x-5x+6

Add 8 to each side

x-8+8 = 6+8

x=14


b.  4x-3 = 2(x-1)

Distribute

4x-3 =2x-2    He changed the sign on the 2

Subtract 2x from each side

4x-2x -3 = 2x-2x-2

2x-3 =-2

Add 3 to each side

2x-3+3 =-2+3

2x =1

Divide by 2

2x/2 =1/2

x=1/2